DESIGN AND BUILD A COCONUT HUSK CHOPPER MACHINE USING AN 8 HP GASOLINE ENGINE - Muchlisinalahuddin, Muchlisinalahuddin; Apriyadi, Yudi; Arief, Rudi Kurniawan (Department of Mechanical Engineering Education, 2023)
The coconut frond cutter or coconut frond shredder is a device used to transform coconut fronds into small pieces, even turning them into a finely textured material. This study examines the design and development of a coconut-chopping machine that uses an 8 HP combustion motor. Structural analysis was performed on the machine frame by considering the maximum and minimum Von Mises Stresses. The analysis results show that the maximum Von Mises Stress in the frame is 1.670e+06 N/mm², while the minimum stress is 2.338e+04 N/mm². The displacement of the frame was observed at 2.642e-02 mm to 1.000e-30 mm. The safety factor of the frame was found to be 1.366e+02, indicating an adequate level of safety. Next, this study analyzed the shredding capacity of the machine. The analysis showed that the largest shredding capacity was 3619.30 kg/hour, which occurred at a high rotation of young fronds, producing fine shreds. Meanwhile, the smallest shredding capacity of 612.66 kg/hour occurs at low rotation of old fronds and produces coarse shreds. These results provide essential insights into using coconut shredding machines based on the rotation level and the processed material. This research contributes to the development of efficient and effective coconut processing technology.